MANAJEMEN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN DAN KINERJA GURU MELALUI PEMBELAJARAN YANG EFEKTIF - Fauziah, Ana Laila (Wali Pikir: Journal Of Education, 2023)
This research aims to obtain an overview and information about the transformational leadership management of school principals in improving teacher discipline and performance in learning which includes: 1) planning, 2) organizing, 3) implementation, 4) supervision, and 5) evaluation. The research method used is descriptive qualitative. Data collection was obtained from information, places and activities of the school principal’s leadership activities, as well as documents. Data collection techniques include interviews, observation and document study. Data validity testing was carried out by applying source triangulation and method triangulation. The data analysis technique is in the form of an interactive analysis technique, namely data reduction, data display, and conclusion drawing which interact with each other. Transformational leaders have the ability to align their vision of the future with their subordinates, as well as raise the needs of subordinates at a higher level than they need. The research results consist of the main findings, namely: 1) the three madrasas have a vision, mission, strategy and goals as an indication of the clear direction of a learning plan; 2) The school principal can provide attention in the form of facilities in the teaching and learning process, provide solutions, provide main duties, and provide motivation to teachers who meet targets; 3) The principal’s transformational leadership management does not work as it should, but teacher discipline and performance can run well even though it is not as expected; 4) monitoring and evaluation of the three madrasas that have implemented transformational leadership management well, although not yet optimally.